Layered Double Hydroxide Coated by Carbon-Based Material for Environmental Dye Pollutant - Neza Rahayu Palapa; Alfan Wijaya (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2023)
We conducted this research to modify NiAl layered double hydroxide with several carbon-based materials, including cellulose, biochar and graphite. This material was successfully prepared by coprecipitation methods and was proven by XRD, SEM and FTIR characterization. Furthermore, we conducted the adsorption process and reusability to investigate their ability as water treatments. The dose effect on M.G. removal was investigated by the highest M.G. removal capacity using the CBC-NiAl LDHs composite, which was 100 mg. M.G. removal capacity was increased with an increase in contact time, and the saturation point was reached after 60 min for CC-NiAl and CGF-NiAl LDHs, which CBC-NiAl LDH increased and saturated after 100 min with high adsorption capacity. CC-NiAl, CBC-NiAl and CGF-NiAl LDHs composite have proved efficient, sustainable materials that maintain adsorption capability in each reusable cycle.